Development of Lithium-Stuffed Garnet-Type Oxide Solid Electrolytes with High Ionic Conductivity for Application to All-Solid-State Batteries - Inada, Ryoji; Yasuda, Satoshi; Tojo, Masaru; Tsuritani, Keiji; Tojo, Tomohiro; Sakurai, Yoji (Frontiers in Energy Research, 2016)
All-solid-state lithium-ion batteries are expected to be one of the next generations of energy storage devices because of their high energy density, high safety, and excellent cycle stability. Although oxide-based solid electrolyte (SE) materials have rather lower conductivity and poor deformability than sulfide-based ones, they have other advantages, such as their chemical stability and ease of handling. Among the various oxide-based SEs, lithium-stuffed garnet-type oxide, with the formula of Li7La3Zr2O12 (LLZ), has been widely studied because of its high conductivity above 10−4 S cm−1 at room temperature, excellent thermal performance, and stability against Li metal anode. Here, we present our recent progress for the development of garnet-type SEs with high conductivity by simultaneous substitution of Ta5+ into the Zr4+ site and Ba2+ into the La3+ site in LLZ. Li+ concentration was fixed to 6.5 per chemical formulae, so that the formula of our Li garnet-type oxide is expressed as Li6.5La3−xBaxZr1.5−xTa0.5+xO12 (LLBZT) and Ba contents x are changed from 0 to 0.3. As a result, all LLBZT samples have a cubic garnet structure without containing any secondary phases. The lattice parameters of LLBZT decrease with increasing Ba2+ contents x ≤ 0.10 while increase with x from 0.10 to 0.30, possibly due to the simultaneous change of Ba2+ and Ta5+ substitution levels. The relative densities of LLBZT are in a range between 89 and 93% and are not influenced in any significant way by the compositions. From the AC impedance spectroscopy measurements, the total (bulk + grain) conductivity at 27°C of LLBZT shows its maximum value of 8.34 × 10−4 S cm−1 at x = 0.10, which is slightly higher than the conductivity (= 7.94 × 10−4 S cm−1) of LLZT without substituting Ba (x = 0). The activation energy of the conductivity tends to become lower by Ba substation, while excess Ba substitution degrades the conductivity in LLBZT. LLBZT has a wide electrochemical potential window of 0–6 V vs. Li+/Li, and Li+ insertion and extraction reactions of TiNb2O7 film electrode formed on LLBZT by aerosol deposition are demonstrated at 60°C. The results indicate that LLBZT can potentially be used as a SE in all-solid-state batteries.